Trusted FPGA‐based transport traffic inject, impersonate (I2) attacks beaconing in the Internet of Vehicles. Issue 3 (1st May 2019) - Appathurai, Ahilan; Manogaran, Gunasekaran; Chilamkurti, Naveen
Abstract : Internet of Things assisted vehicular ad‐hoc network VANET (I‐VANET) is one of the preferred technologies to provide fast and reliable communication in smart transportation systems. With the goal of preserving security, I‐VANET is characterised by field‐programmable gate array‐based remote dynamic partial reconfiguration (RDPR) and security providing entity as a washable physical unclonable function (WPUF). In this specific work, an efficient WPUF‐based unknown authentication scheme is proposed to identify and avoid malicious vehicles entering into the I‐VANET. In addition to that, the proposed work provides a conditional tracing mechanism to hint the vehicles or roadside units that misuse the I‐VANET. This system reveals the malicious vehicles to efficiently provide conditional privacy through I‐VANET, by enabling a situation where the entities are unknown to each other until they depart from the network. Finally, I 2 attacks were analysed from possible attacks that can emanate from the availability of RDPR at I‐VANET nodes, and WPUF circuit was used to prevent such attacks. The proposed WPUF‐based authentication scheme takes only around 120 ms for verifying 100 tokens but other conventional techniques take >900 ms for verifying 100 tokens.